Transactional and Interpersonal Conversation Texts in English Textbook - Ulin Nuha (UIN Salatiga, 2014)
In this study, The researcher analyzed the transactional andinterpersonal conversation texts found in grade VIII English textbookentitled ―EOS English on Sky 2‖ and I also analyzed the linguisticfeatures of the transactional and interpersonal conversations in theEnglish textbook. This study focuses on the issues of structuralfunctionalapproach which analyzes the speech function, structuralapproach which analyzes linguistic features. This is a qualitative study.In calculating the data and the final result of data percentage,quantification was used to support this study. Units of analysis in thisstudy are moves and clauses. The conversation texts are presented in 8units. The moves were analyzed functionally and the clauses wereanalyzed structurally. The result shows that the speech functions of thetransactional conversation texts are 54.5% matching the standard ofcontent, the speech functions of the interpersonal conversation texts are2.1% matching the standard of content. The linguistic feature applied inthe transactional and interpersonal conversation texts uses the linguisticfeature in functional literacy level. The speech functions of conversationtexts introduced in EOS English on Sky 2 for junior high school grade VIII are less compatible with the standard of content based on thecompatibility levels. Keywords: Transactional and interpersonal conversation texts; Speech function; linguistic feature.